Impulsive Internet Game Play Is Associated With Increased Functional Connectivity Between the Default Mode and Salience Networks in Depressed Patients With Short Allele of Serotonin Transporter Gene - Hong, Ji Sun; Kim, Sun Mi; Bae, Sujin; Han, Doug Hyun (Frontiers in Psychiatry, 2018)
Background Problematic internet game play is often accompanied by major depressive disorder (MDD). Depression seems to be closely related to altered functional connectivity (FC) within (and between) the default mode network (DMN) and salience network. In addition, serotonergic neurotransmission may regulate the symptoms of depression, including impulsivity, potentially by modulating the DMN. We hypothesized that altered connectivity between the DMN and salience network could mediate an association between the 5-HTTLPR genotype and impulsivity in patients with depression. A total of 54 participants with problematic internet game play and MDD completed the research protocol. We genotyped for 5-HTTLPR and assessed the DMN FC using resting-state functional magnetic resonance imaging. The severity of internet game play, depressive symptoms, anxiety, attention and impulsivity, and behavioral inhibition and activation were assessed using the Young Internet Addiction Scale (YIAS), Beck Depressive Inventory, Beck Anxiety Inventory (BAI), Korean Attention Deficit Hyperactivity Disorder scale, and the Behavioral Inhibition and Activation Scales (BIS-BAS), respectively. The SS allele was associated with increased FC within the DMN, including the middle prefrontal cortex (MPFC) to the posterior cingulate cortex, and within the salience network, including the right supramarginal gyrus (SMG) to the right rostral prefrontal cortex (RPFC), right anterior insular to right SMG, anterior cingulate cortex (ACC) to left RPFC, and left anterior insular to right RPFC, and between the DMN and salience network, including the MPFC to the ACC. In addition, the FC from the MPFC to ACC positively correlated with the BIS and YIAS scores in the SS allele group. The SS allele of 5-HTTLPR might modulate the FC within and between the DMN and salience network, which may ultimately be a risk factor for impulsive internet game play in patients with MDD.